Design-for-test using scan path technique - 374163 Wang, Wee Ming (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering (Electronic)) - Universiti Teknologi Malaysia, 2001